Correlation of B-mode and Doppler Ultrasound Parameters of Kidney with Serum Creatinine Level in Chronic Kidney Disease Patients - Jabin, Prianka; Nasreen, Faria; Hassan, Md Mahmudul; Salma, Ummme; Konik, Tasnia Kawsar; Purveen, Rejuana; Roy, Sutanu (Bangladesh Journal of Nuclear Medicine, 2024)
Abstract not available Bangladesh J. Nuclear Med. 27(1): 62-68, 2024